Comparison of Virosome vs. Liposome as drug delivery vehicle using HepG2 and CaCo2 cell lines. (4th July 2021) - Kumar, Varun; Kumar, Ramesh; Jain, V. K.; Nagpal, Suman
Abstract: Aim: The present work involves encapsulation of herbal drug nanocurcumin into the virosomes and compared with a liposome in terms of their in vitro anti-proliferative, anti-inflammatory, and anti-migratory efficacy. Methods: The anti-proliferative, anti-inflammatory, and anti-migratory efficacy of virosome and liposome were compared in HepG2 and CaCo2 cells by using MTT, Nitric oxide scavenging, and Wound healing assay, respectively. Results: Size of the optimised NC-Virosome and NC-Liposome was 70.06 ± 1.63 and 265.80 ± 1.64 nm, respectively. The prepared NC-Virosome can be stored at −4 °C up to six months. The drug encapsulation efficiency of NC-Virosome and NC-Liposome was found to be 84.66 ± 1.67 and 62.15 ± 1.75% (w/w). The evaluated minimum inhibitory concentration (IC50 value) for NC-Virosome was 102.7 μg/ml and 108.1 μg/ml, while NC-Liposome showed 129.2 μg/ml and 160.1 μg/ml for HepG2 and CaCo2 cells, respectively. Morphological examination depicts detachment of the cells from substratum after exposure to NC-Virosome for 48 h. Conclusion: The prepared NC-Virosome provides remarkable in vitro efficacy in both the cell lines with site-specific drug-targeting potential as compared to the liposome, results proved its potential as a drug delivery vehicle for future therapy with reduced toxicity.